PENERAPAN ACTIVITY BASED COSTING PADA TARIF JASA RAWAT INAP RUMAH SAKIT (Studi Pada Rumah Sakit Wiyung Sejahtera Surabaya) - Jayanti, Neni (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out how the determination of inpatient tariff has been done by using activity based costing at Wiyung Sejahtera Hospital Surabaya and to find out the great comparison of the inpatient tariff by using accounting based costing and traditional cost accounting. Qualitative method is used as the research method. The data which have been obtained from the hospital only include the 2012 data and the determination of inpatient tariff which is going to be studied is the general treatment type for room tariff only. The result of the research shows that inpatient service tariff which has been done by using activity based costing system has been performed through two stages. On the first stage, the cost is traced to the activities which generate costs and on the second stage the hospital charges activity costs to product. The calculation of inpatient service tariff which has been done by using ABC (Accounting Based Costing) has found the amount of room tariff for VVIP class is Rp 550,000; VIP class is Rp 500,000; 1st class is Rp 400,000; 2nd class is Rp 350,000; and 3rd class is Rp 325,000.Keywords: Tariff, Inpatient, Activity Based Costing System